Analysis of Work-Life Balance in European Union Countries: The Impact of Technological Progress and Digitalization - Balvociute, Rasa; Salkauskiene, Ligita (European Journal of Sustainable Development, 2025)
The 2030 Agenda for Sustainable Development, approved by the United Nations, includes two important goals related to work-life balance: ensuring healthy lives for everyone and promoting sustainable economic growth. A key part of sustainable economic growth is providing full, productive jobs with good working conditions. Recent research shows that work-life balance has several critical issues. Long working hours and heavy workloads are major concerns that harm both physical and mental health. Poor work-life balance can lead to stress, burnout and lower productivity. It's important to maintain a good work-life balance not just for employees’ health, but also for the success of organizations. Companies that support work-life balance have more engaged employees, greater loyalty and lower turnover rates. The rapid growth of technology in the workplace, at home and in public life affects how employees balance work-life time. Cultural differences, economic conditions and social policies impact work-life. This study aims to improve the understanding of work-life balance in EU countries as technology advances. It will identify key factors influencing this balance and explore future trends. The research uses EUROSTAT data to look at work-life balance across 27 EU countries from 2005 to 2023, utilizing regression analysis models for panel data. Keywords: work-life balance, technological progress, digitalization, healthy life